2021
DOI: 10.1007/s00264-021-05153-8
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and aetiology of male and female sexual dysfunctions related to pelvic ring injuries: a systematic review

Abstract: Introduction Pelvic ring injuries, frequently caused by high energy trauma, are associated with high rates of morbidity and mortality (5–33%), often due to significant blood loss and disruption of the lumbosacral plexus, genitourinary system, and gastrointestinal system. The aim of the present study is to perform a systematic literature review on male and female sexual dysfunctions related to traumatic lesions of the pelvic ring. Methods Scopus, Cochrane L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 57 publications
(127 reference statements)
1
25
0
1
Order By: Relevance
“…Patients with anterior and posterior compression-type and vertical shear-type fracture patterns reported a higher incidence and severity of sexual dysfunction. However, only a weak association was found between genitourinary injuries, the occurrence and severity of sexual dysfunction, and the association between surgical treatment and sexual dysfunction [34].…”
Section: Discussionmentioning
confidence: 97%
“…Patients with anterior and posterior compression-type and vertical shear-type fracture patterns reported a higher incidence and severity of sexual dysfunction. However, only a weak association was found between genitourinary injuries, the occurrence and severity of sexual dysfunction, and the association between surgical treatment and sexual dysfunction [34].…”
Section: Discussionmentioning
confidence: 97%
“…15 According to our modern experience, lateral plate and medial strut allograft is the best choice to treat the perimplants failure 16 and periprosthetic femoral fracture. [16][17][18] The cortical strut only allografts confer stability to the fracture site, and they can incorporate and ultimately increase the femoral bone stock. 19 They also "lengthen" the working length of the screws.…”
Section: Orthopedic Reviewsmentioning
confidence: 99%
“…Our studies have suggested that cortical struts predictably unite, remodel, mature and not breakage's risk. [16][17][18][19] To obtain the maximum stability of the metal-biological construct the osteosynthesis with screws should always be used (Figure 1 and Figure 2) because the use of metal cerclage cables can lead to implant failures and subsequent revisions. 22,24 Other authors suggested Total femur replacements or a megaprosthesis are typically reserved for patients with lim-ited bone stock and loose implants or in the situation of multiple failed fracture fixation or persistent fracture nonunion, revision to a megaprosthesis may provide a route to definitive treatment.…”
Section: Orthopedic Reviewsmentioning
confidence: 99%
“…Screw penetration of the bone cortex may damage the lumbosacral plexus nerves, internal iliac vessels, genitourinary system and gastrointestinal system, and due to significant blood loss and disruption of the lumbosacral plexus, genitourinary system and gastrointestinal system, severe consequences of massive hemorrhage may lead to death [ 5 ]. Injury of lumbosacral plexus nerves and genitourinary system may lead to sexual dysfunctions with important influence on quality of life, especially in young patients [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the development of orthopedic navigation technology, some scholars have applied navigation technology to insert fixation screws in pelvic fractures [ 7 ]. Ciolli et al inserted percutaneous screws of the anterior ring internal fixator system by navigation system based on 3D fluoroscopic images, and the conclusion is that the use of the O-arm deals with great precision in the positioning of the screw and reduced surgical times with excellent clinical results in patients [ 6 ]. However, navigation technology requires special intraoperative imaging system, and surgery requires longer learning curves.…”
Section: Introductionmentioning
confidence: 99%